2014
DOI: 10.1007/s00221-014-4167-7
|View full text |Cite
|
Sign up to set email alerts
|

Sonification and haptic feedback in addition to visual feedback enhances complex motor task learning

Abstract: Concurrent augmented feedback has been shown to be less effective for learning simple motor tasks than for complex tasks. However, as mostly artificial tasks have been investigated, transfer of results to tasks in sports and rehabilitation remains unknown. Therefore, in this study, the effect of different concurrent feedback was evaluated in trunk-arm rowing. It was then investigated whether multimodal audiovisual and visuohaptic feedback are more effective for learning than visual feedback only. Naïve subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 98 publications
(157 reference statements)
5
126
0
3
Order By: Relevance
“…A highly specialized training system for rowing in VR is presented by Sigrist et al [2014]. The user is placed in a modified boat, surrounded by projection walls.…”
Section: Related Approachesmentioning
confidence: 99%
“…A highly specialized training system for rowing in VR is presented by Sigrist et al [2014]. The user is placed in a modified boat, surrounded by projection walls.…”
Section: Related Approachesmentioning
confidence: 99%
“…Este tipo de estímulo tiene un interés especial en la búsqueda de un mejor desempeño de la tarea motora a través del principio de acción-reacción (21).…”
Section: Entrenamiento Motorunclassified
“…A partir de estos circuitos, el usuario elige y ejecuta el patrón motor activando los grupos musculares que correspondan a la tarea funcional definida por el fisioterapeuta (21).…”
Section: Entrenamiento Motorunclassified
“…However, multimodality does not come without its drawbacks in motor learning. Sigrist et al [53], for example, indicated in their study that multimodality is likely only limited in its advantages in cases in which the motor task is complex in nature. Qualities often attributed to the most effective forms of multimodal feedback in motor learning systems include accuracy, customizability, and measurability [54,55].…”
Section: Modality Selection and Mappingmentioning
confidence: 99%
“…As motor tasks are often repetitive in nature, the rhythmic nature of audio can be exploited to correct a user's motion in the temporal domain [59]. It has been shown to combine well with haptic and visual feedback under these assumptions [53].…”
Section: Audiomentioning
confidence: 99%